Sites of qualification: the motorcycle rider airbag and the production of safety. Issue 1 (2nd January 2021) - Reimer, Suzanne; Pinch, Philip
ABSTRACT: The paper mobilises the distinctive notion of 'sites of qualification' as a means of providing an expansive understanding of how innovative products are designed, produced and brought to consumer markets. We focus on the development of a new safety product for motorcyclists, the rider airbag, in which inflatable body protection is either incorporated into, or worn underneath, textile jackets and leather suits. The paper follows the airbag's trajectory across a range of different sites, including lead firms and their territorial settings; MotoGP racetracks, mobile laboratories and professional riders; courts of law; and showroom and archive locations. The paper's sites of qualification approach expands understandings of innovation by constructing a dialogue between two sets of literatures: actor-network approaches to the qualification of products; and narratives which understand economic innovation as emerging through clusters of agents and firms within industrial districts. The conclusion emphasises that sites of qualification are integral to the ways in which technical products such as the rider airbag are made social.